Inside London's airports policy : indecision, decision and counter-decision - Le Blond, Paul (ICE Publishing, 2018)
Inside London's Airports Policy provides a complete history of London's airport policy, and asks if we can learn from the lessons of history. Based on the author's extensive industry experience, and detailed research of key documents, public records and academic papers, plus interviews with key individuals, the book sets out the studies, consultations, inquiries, commissions and debates that have directed London's Airport policy. The book covers in detail a period from the mid-1970s, when the Maplin project was cancelled, to the present day. Along the way, there are periods of incremental growth with new terminals at Heathrow, Gatwick and Stansted; a policy vacuum of the early 1990s and the Heathrow Terminal 5 Inquiry; a long term strategy outlined in the 2003 White Paper; and the Airports Commission of 2012-2015.
Keywords: Airports -- Government policy -- Great Britain.; Airports -- England -- London.; Aeronautics and state -- Great Britain.; elektronické knihy; electronic books